2019
DOI: 10.34050/els-jish.v2i4.8354
|View full text |Cite
|
Sign up to set email alerts
|

Assertive Illocutionary Act Adapted in Donald Trump’s Political Speech: A Pragmatic Study

Abstract: This research is intended to discuss the illocutionary acts used in a speech mainly assertive. The writer attempts to analyze the categories of assertive illocutionary act occurs in the utterances of Donald Trump’s political speech in last America’s general election. This is a case study that employed a qualitative method with a descriptive approach. The writer uses Ancont software to classify the data. The function of this software is to observe the frequent words occur in the data. Then, it shows that the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In addition, the results of this study have differences and similarities to research conducted by (Ramadhani et al, 2019), which found that assertiveness is the most common type of illocutionary act.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…In addition, the results of this study have differences and similarities to research conducted by (Ramadhani et al, 2019), which found that assertiveness is the most common type of illocutionary act.…”
Section: Discussionmentioning
confidence: 38%
“…The researchers used the theories from Searle (1975) and Hymes (1977), and the result showed the dominant use of illocutionary act in the movie was directive. The third research that also discussed the illocutionary act was conducted by (Ramadhani, Indrayani, & Soemantri, 2019). The study mainly focused on observing the frequent category of assertive in Donald Trump's speech.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Ramadhani et al (2019) on a speech of Donald Trump, through analysis, Trump's political speech is a statement of assertion and fact where he attempts to represent himself and convince citizens with facts about the problem that he believes to be the case to establish a positive image toward his arguments. Larasati et al (2020) concluded in their Illocutionary Speech Acts analysis of Trump's Presidential Candidacy Speech that he mainly produced the assertive type of Illocutionary Acts in his speech.…”
Section: Research Questionsmentioning
confidence: 99%
“…Next, the research was done by (Ramadhani, Indrayani, & Soemantri, 2019). Their research also the same to analyzse the type or categories of assertive acts found in Donald Trrump's political speech.…”
Section: Introductionmentioning
confidence: 99%